THE MILK QUALITY OF PERANAKAN ETAWAH (PE) GOAT DURING STORAGE AT ROOM TEMPERATURE TO PHYSICOCHEMICAL AND MICROBIOLOGICAL PROPERTIES - D.N., Hariyanto; Okarini, I. A.; Suryani, N.N. (Jurnal Peternakan Tropika, 2021)
Milk is one of the livestock products that has a complete and balanced nutritional content. Each type of milk has different qualities depending on its physical, chemical, and microbiological properties. This study aims to determine the milk quality of peranakan etawah (PE) at different time storage at room temperature in terms of physicochemical and microbiological properties. Milk samples were obtained from peranakan etawah (PE) farms in Sepang Village, Busung Biu District, Buleleng Regency. The research was conducted for one month from June to July 2018. The design used was a completely randomized design consisting of  3 treatments and 4 replications. The three treatments were 0 hours of storage time (L0), 4 hours of storage time (L4), and 6 hours of storage time (L6), so that there were 12 experimental units. The variables observed in this study were total acid, specific gravity, color, and coliform bacteria. Data obtained from this study were analyzed using annova, if there were significant differences (P<0.05) the analysis was continued by Duncan's multiple range test. The results showed that the different specific gravity was not significant (P>0.05), while the duration of L4 and L6 storage respectively in the total acid test (20.00% and 26.45%) and the number of coliform bacteria (44.26% and 36.59%) showed a significant increase (P<0.05). For milk color significantly decreased (P<0.05), where L4 (5.47%) and L6 (6.61%) were lower than L0. Based on the results of the study it can be concluded that the specific gravity is not affected, while the total acid, milk color, and coliform bacteria are affected by the storage time at room temperature. The value of total acid, specific gravity, and milk coliform bacteria increases, while the color value decreases with storage time at room temperature Key words: quality of PE goat milk, storage time, physicochemical, microbiology